Peran diplomasi sebagai cara meningkatkan Pengakuan internasional terhadap posisi suatu Negara dalam mengimplementasikan kebijakan politik luar negeri (Studi kasus di Indonesia) - Sofia Martauli (Jurnal Good Governance, 2017)
Economic benefits are increasingly seen as important in the relations of two States. Economic diplomacy is understood here as a factor supporting the increasing bilateral trade and investment between the two countries. The law has evolved to support the activities of countries to achieve their national goals. This paper does not use descriptive techniques to illustrate the superiority of diplomatic programs and the performance of foreign ministries in carrying out diplomatic programs. Economic diplomacy as an instrument has been used by Indonesia to improve its export performance to partner countries this is because Indonesia is increasingly dependent on the international market, not only the average ratio of exports to GDP is increasing, but also the average import ratio that shows increase. Diplomacy is also useful to boost cooperation opportunities in order to open markets for food and agricultural products. Indonesia's diplomatic performance has shown strengthening, both in bilateral, regional and multilateral terms. The subsequent multilateral and regional diplomacy efforts to be undertaken by Indonesia should continue to be strengthened by strong bilateral diplomacy.Keywords:Economic diplomacy, multilateral diplomacy, foreign policy